Analysis of Land Cover Change and Projection of Settlement Land in Sepaku District, North Penajam Paser Regency - Sultan, Habil; Rahmalidya, Alfia; Shopura, Adia Wafa; Akmal, Muhammad Roihan; Fariz, Trida Ridho; Haryadi, Haryadi; Lutfiananda, Fathia (Universitas Negeri Semarang, 2022)
The relocation of the capital city of Indonesia to Sepaku District, North Penajam Paser Regency, East Kalimantan will have an impact on all existing aspects. Land cover in Sepaku District has decreased from year to year. The area of vegetated land cover in Sepaku District is assumed to be decreasing due to the relocation of the New Capital City (NCC) to the area, which will have a negative impact on the environment. Therefore, this study aims to determine the level of land cover change in Sepaku District and discuss how the condition of land cover in Sepaku District after the construction of the New Capital City (NCC). The method in this study uses GIS (Geographical Information System) analysis and descriptive analysis. The data used are land cover data from 2009 to 2019 to find out changes in land cover and population data from BPS to project the population. Based on the results of the analysis of land cover data from 2009 to 2019 there was a change from scrubland to industrial forest plantations of around 26000 ha. In addition, there was no significant change in the area of built-up land. However, the results of population projections show that Sepaku Sub-district will experience a significant increase in built-up land cover after the construction of the New Capital City (NCC).